DIGITAL TRANSFORMATION OF ISLAMIC FINANCIAL SERVICES: THE DIRECT IMPACT OF ISLAMIC DIGIBANK AND FINTECH ON TRUST AND INVESTMENT INTEREST - Masalingi, Abdurrahman; Sopingi, Imam (Airlangga International Journal of Islamic Economics and Finance, 2025)
This study investigates the influence of Islamic Digital Banking and Islamic Fintech on trust and investment interest, while also testing the mediating role of trust within these relationships. Employing a quantitative approach with path analysis through the Partial Least Squares (SmartPLS) method, the research involved 123 student members of the Islamic Economic Studies Forum (FoSSEI) in East Java as respondents. The results indicate that both Islamic Digital Banking and Islamic Fintech significantly enhance trust and directly increase investment interest, with trust functioning as a crucial mediator that connects the adoption of sharia-based digital financial services with investment behavior among young Muslims. Theoretically, these findings enrich the body of knowledge in Islamic digital finance by illustrating the interaction between technological innovation and spiritual values in shaping financial decision-making, while practically, they provide recommendations for regulators, financial institutions, and fintech developers to prioritize sharia digital literacy and design inclusive, ethical, and youth-oriented financial platforms. Despite these contributions, the study is limited by its relatively small and localized sample and by the use of cross-sectional data, which may restrict the generalizability of results and prevent observation of behavioral changes over time. Accordingly, future research is encouraged to adopt larger and more diverse samples, employ longitudinal or experimental methods, and consider additional variables such as religiosity, literacy, or risk perception to deepen understanding of Islamic digital finance. Overall, the research highlights that trust serves as a strategic cornerstone in linking Sharia-compliant financial technology with sustainable investment participation. Keywords: Investment Interest, Islamic Digital Banking, Islamic Fintech, Path Analysis, Trust